Breast cancer screening in developing countries - da Costa Vieira, René Aloísio [UNESP]; Biller, Gabriele; Uemura, Gilberto [UNESP]; Ruiz, Carlos Alberto; Curado, Maria Paula (Elsevier, 2017)
Developing countries have limited healthcare resources and use different strategies to diagnose breast cancer. Most of the population depends on the public healthcare system, which affects the diagnosis of the tumor. Thus, the indicators observed in developed countries cannot be directly compared with those observed in developing countries because the healthcare infrastructures in developing countries are deficient. The aim of this study was to evaluate breast cancer screening strategies and indicators in developing countries. A systematic review and the Population, Intervention, Comparison, Outcomes, Timing, and Setting methodology were performed to identify possible indicators of presentation at diagnosis and the methodologies used in developing countries. We searched PubMed for the terms “Breast Cancer” or “Breast Cancer Screening” and “Developing Country” or “Developing Countries”. In all, 1,149 articles were identified. Of these articles, 45 full articles were selected, which allowed us to identify indicators related to epidemiology, diagnostic intervention (diagnostic strategy, diagnostic infrastructure, percentage of women undergoing mammography), quality of intervention (presentation of symptoms at diagnosis, time to diagnosis, early stage disease), comparisons (trend curves, subpopulations at risk) and survival among different countries. The identification of these indicators will improve the reporting of methodologies used in developing countries and will allow us to evaluate improvements in public health related to breast cancer.
Keywords: Breast neoplasms; Developing country; Epidemiology; Mammography; Mass screening; Prevention & control